CO2 Monitoring System Prototype using Wireless Sensor Network - Hanif Arief Wisesa (International Journal on Information and Communication Technology (IJoICT), 2016)
An abstract of no more than 200 words should state the purposes of the study, procedures, findings and conclusions. It should be written in Times New Roman with font size of 9. Abstract should be followed by four to eight key words to assist cross-indexing. The key words should be ordered alphabetically and separated by commas. For your paper to be published in the journal, you must use this document as both an instruction set and as a template into which you can type your own text. If your paper does not conform to the required format, you will be asked to fix it. In the paper, authors are suggested to present their articles in the sections structure: Introduction - Previous Study/Literature Review - The Proposed Method/Algorithm/Procedure specifically designed (optional) - Research Method Results and Discussion - Conclusion. Authors may present complex proofs of theorems or non-obvious proofs of correctness of algorithms after introduction section (obvious theorems and straightforward proofs of existing theorems are not needed).Â